EUNOIA DALAM FINE ART PHOTOGRAPHY - Hafizah, Harizona (Matalensa: Journal of Photography and Media, 2021)
Every human being has emotions that can feel happy, sad, or angry. However, negative emotions are often felt in everyday life by someone due to their busy schedule, departing from personal experience, so they are interested in bringing them up into the creation of a thesis. Eunoia is positive thoughts conveyed to others. The purpose of the creation of this thesis is the creation of Fine Art Photography that can motivate and change one's mood (feelings) to be more positive. The creation of this photo work is carried out in four stages, first in the form of preparation by conducting research and finding ideas, secondly designing the concept of the work, the third embodiment of the work, and fourthly presenting the work. The concept used in the work is taken from three aspects, namely humans, animals and nature. By using negative photo effect editing, the work has an optical illusion that can give the sensation of enjoying a different work